Electrochemical Epitaxial Grown PbS Nanorods Array on Graphene Film for High‐Performance Photodetector. Issue 1 (16th November 2020) - Yang, Chan; Feng, Shuanglong; Tang, Linlong; Shen, Jun; Wei, Xingzhan; Shi, Haofei
Abstract: PbS based low dimensional heterostructures have shown promising IR photodetector applications, arising from the multiple exciton effect. However, owing to the difficulty in controlling the size, shape, nucleation, and growth of PbS nanorods, it remains a significant challenge to construct PbS nanorods array heterostructures with precisely controlled orientation, morphology, dimensionality, and spatial distribution of each component. Here, an electrochemical atomic layer epitaxial growth method is reported to prepare the PbS nanorods array‐graphene heterostructures by engineering the structures, sizes, dimensionalities, and morphologies lattice parameters of PbS. In these heterostructures, PbS nanorods selectively grow along (200) orientation on graphene film by adjusting the underpotential deposition. The high‐oriented PbS nanorods‐graphene heterostructure's growth dynamics are confirmed by comparing the extreme polarization of graphene, resulting in controllable growth orientation and nucleation. Furthermore, the PbS nanorods‐graphene heterostructure photodetector presents an extraordinary photoresponsivity in exceeding 10.4 A W −1 and figure‐of‐merit detection D * ≈ 2.98 × 10 9  Jones is demonstrated in 2.7 µm at room temperature. The selective epitaxial growth of PbS nanorods opens the way to synthesize different hierarchical heterostructures with tunable architectures and dimensionalities, which can process various promising applications. Abstract : In this work, an electrochemical atomic layer epitaxy growth method is reported to prepare the highly oriented (200) PbS nanorods array on graphene film by adjusting the underpotential deposition. The PbS nanorods‐graphene heterostructure photodetector presents an extraordinary photoresponsivity in exceeding 10.4 A W −1 and detectivity of ≈2.98 × 10 9  Jones in 2.7 µm at room temperature.